(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The relevance of the present study is determined by several factors’ characteristic of contemporary educational practice. Research findings indicate that a considerable proportion of conflicts in educational institutions are associated with insufficient managerial competence and ineffective communication processes